PROPAGANDA SIMBOL DAJJAL DALAM BUDAYA VISUAL JEPANG: ANALISIS SEMIOTIKA FILM YU-GI-OH! THE MOVIE – HIKARI NO PYRAMID - Bintoro Wibisono, Muhammad; Saefullah, Aris (Hujjah: Jurnal Ilmiah Komunikasi dan Penyiaran Islam, 2025)
The objective of this research is to pinpoint and scrutinize the symbolic depictions of the antichrist figure, often known as Dajjal, as they appear in the Japanese anime film Yu-Gi-Oh! The Movie – Pyramid of Light, with the intention of deciphering the underlying ideological messages embedded within the movie. This study adopts a qualitative methodology, employing Charles Sanders Peirce's semiotic analysis to concentrate on both spoken and unspoken cues, including icons, indexes, and symbols. Information was gathered by means of visual documentation, specifically screen captures from the film, and subsequently examined descriptively to expose the underlying system of signs employed. The results of the research highlight the presence of eleven symbols associated with the depiction of Dajjal, comprising two verbal symbols and nine nonverbal symbols. These symbols construct a visual narrative that alludes to themes such as the singular eye, the illumination of darkness, and supernatural capabilities, which are understood as a symbolic form of propaganda related to the religious idea of the antichrist. The findings indicate that widely enjoyed films, such as anime, have the potential to serve as conduits for spreading specific ideological symbols that shape viewers' perceptions of spiritual and moral principles. Consequently, semiotic analysis of popular works is crucial for comprehending the ways in which religious meanings are portrayed and disseminated through worldwide visual culture. The qualitative approach is employed as the research method for this thesis. The investigation took place in libraries and at home, spanning from March to May 2016. The researcher used a method of gathering data through documentation consisting of images for this research. A laptop, relevant books, and internet connection served as tools for the researcher in this investigation.This thesis research employs a qualitative approach. The research was conducted in libraries and at home from March to May 2016. For this study, the researcher used documentary data collection methods focusing on image data. The research tools included an Acer laptop, books relevant to the research subject, and internet access. The research subject comprises the symbols of Dajjal found in the Japanese anime film Yu-Gi-Oh! The Pyramid of Light. Data processing was conducted qualitatively by classifying the symbols identified in the film Yu-Gi-Oh! The Pyramid of Light. Data analysis was performed using Charles Sanders Peirce's semiotic analysis, specifically analyzing verbal and non-verbal symbols, as well as analyzing iconic signs within the Dajjal symbols in Yu-Gi-Oh! The Pyramid of Light. The analysis is presented both in tabular and descriptive forms. Based on the findings and analysis of the collected data, the researcher concludes the following: Eleven symbols were identified, consisting of 2 verbal symbols and 9 non-verbal symbols. All symbols contain icons associated with Dajjal. Keywords: Propaganda, Dajjal Symbols, Film Yu-Gi-Oh! The Pyramid of Light